PERSEPSI GURU BIOLOGI SEKOLAH MENENGAH ATAS (SMA) TERHADAP KURIKULUM 2013 - Isthofiyani, Sri Endhes; Budi Prasetyo, Andreas Priyono; Sukaesih, Sri (Journal of Biology Education, 2014)
The change of curriculum raises a number of perceptions which can be devided into two classifications, namely: the affirmative (pros) and the negative (cons). However, there is only a little information about teachersâ perceptions itself. The teachersâ perceptions influence on learning behaviors that are important in determining the success of a curriculum innovation. This research aims to describe the perceptions or the beliefs of Biology teachers to the 2013 Curriculum. This research was a survey to all grade X Biology teachers that conducted at several high schools in Semarang during the second semester of academic year 2012/2013. The total sample was determined by the Isaac and Michaelâs formula and they were taken randomly. The data were taken using the instrument of psychological scale questionaire about high school Biology teachersâ perceptions to the 2013 Curriculum. The results showed that 60% of high school Biology teachers in Semarang had a strong belief in the 2013 Curriculum and 40% of the teachers have a moderate belief. The teachers believed that 2013 Curriculum had its benefits, easily implemented and the teachers were able to implement the curriculum.Perubahan kurikulum menimbulkan dua pendapat, yaitu pendapat yang setuju (pro) dan pendapat yang menolak (kontra). Namun, masih sedikit informasi mengenai persepsi atau beliefs dari guru biologi sendiri. Persepsi guru berpengaruh pada perilaku pembelajarannya yang penting dalam menentukan keberhasilan suatu inovasi kurikulum. Penelitian ini bertujuan untuk mendeskripsikan persepsi atau beliefs guru biologi SMA terhadap Kurikulum 2013.Â  Penelitian ini merupakan penelitian survei yang dilakukan terhadap guru biologi SMA kelas X se-Kota Semarang pada Semester Genap tahun ajaran 2012/2013. Jumlah sampel ditentukan dengan rumus Isaac dan Michael dan sampel diambil secara acak. Data diambil menggunakan instrumen kuesioner skala psikologi tentang persepsi guru biologi SMA terhadap Kurikulum 2013. Hasil penelitian menunjukkan 60%Â  guru biologi di SMA se-Kota Semarang memiliki tingkat persepsi yang tinggi terhadap Kurikulum 2013 dan 40% memiliki tingkat persepsi sedang. Guru meyakini bahwa Kurikulum 2013 memiliki manfaat, mudah dilaksanakan dan guru mampu untuk melaksanakan kurikulum.